CraftDesign for entrepreneurship, social innovation and sustainability - Sendra, Dalia; Ferreira, Ana Margarida (My University, 2021)
Crafts, under the umbrella of the cultural and creative sector, represent an important contribution to social development and cultural freedom. Entrepreneurship through crafts and design brings a strategy to promote the empowerment of vulnerable communities. Given the challenges our society is and will be confronting in the 21st century, such as the climate emergency, the process of digital automation in the human workforce, emergencies such as natural disasters or protracted crises, as well as the socioeconomic crisis that will follow the COVID-19 pandemic, scientific knowledge on policies and strategies aimed at promoting sustainable development and ensuring the equality and social inclusion of vulnerable communities should be strengthened. This paper reflects upon the role crafts design and entrepreneurship can play in promoting sustainable development.
Keywords: Sustainability; Entrepreneurship; Women's Empowerment; CraftsDesign; Social Innovation